NEW MEDIA, CRITICAL ELT AND THE DECONSTRUCTION OF POPULAR CULTURE MENTALITY - Nwode, Goodluck Chigbo; Obinna, Nancy Ngozi; Anyanwu, Edith Ada; Eze, Ugochukwu Christie (EBSU Journal of Social Sciences and Humanities, 2023)
The notion of popular culture stems from misleading rhetoric and orientation of the bourgeoisie of the so-called popular cultures against underdeveloped, poorly developed, non-projected and growing cultures. This study seeks to show that popular culture mentality can be deconstructed through Critical English Language teaching (CELT) and effective use of new media. Observation and secondary data are relied on. Content analysis, systematic review and descriptive tools are employed. The analysis demonstrates that since the construction of popular culture mentality involves media, rhetoric and stereotypical expressions by individuals and groups, its deconstruction can be attained through CELT, which also involves critical literacy and new media use. Through CELT and new media, the masses get educated that no culture is better than or superior to another. They also realise that bourgeois cultural constructs and orientation, and significant exploration and harnessing of any culture are what make the difference between the so-called popular cultures and the others. The study concludes that popular culture mentality can be deconstructed through CELT literacy and new media, because they have far-reaching impact on the audience. It recommends the reorientation of all and sundry, especially young people, about the myths and realities of popular culture. Owners of the labelled unpopular cultures should turn a new leave and do all that would make theirs popular too.